Ripensare la giustizia transgenerazionale attraverso l’immaginazione morale e l’esperienza estetica - Giulia Beltritti (Rivista di Estetica)
The purpose of this article is to highlight how R. M. Hare’s theory can provide important food for thought in dealing with issues related to transgenerationality. In this sense, both the universalization of moral judgments and the imagination, characteristics that, constitute the pillars of Hare’s philosophical theory, provide a key that allows us to place at the center of the moral decision not only the interests of those who inhabit the earth at this time, but also those of all other moral subjects who will exist in a future time.